Новые виды низших орибатид надсемейства Nothroidea (Oribatei, Archoribatida) из Украины - Сергиенко, Г.Д.; Меламуд, В.В. (Вестник зоологии, 1993)
Notherus mirabilis sp. n. is described from Lvivska Oblast. Tri-malaconothrus mirabilis sp. n.— from Ukrainian Carpathian Mts., Malaconothrus laetus sp. n.— from Luganska Oblast. Types are deposited in Schmalhausen Institute of Zoology (Kiev).